Preoperative cognitive function predicts survival in patients with resectable pancreatic ductal adenocarcinoma. Issue 3 (March 2016) - Baekelandt, Bart M.G.; Hjermstad, Marianne J.; Nordby, Tom; Fagerland, Morten W.; Kure, Elin H.; Heiberg, Turid; Buanes, Trond; Labori, Knut J.
Abstract: Background: The purpose of this prospective study was to evaluate whether pre-surgery health-related quality of life (HRQoL) and subjectively rated symptom scores are prognostic factors for survival in patients with resectable pancreatic ductal adenocarcinoma (PDAC). Methods: Patients undergoing pancreatic resection for PDAC completed the Edmonton Symptom Assessment System (ESAS) and the EORTC QLQ-C30 and QLQ-PAN26 questionnaires preoperatively. Patient, tumor and treatment characteristics, recurrence and survival were registered. Results: Sixty-six consecutive patients underwent R0/R1 resection for PDAC. Baseline ESAS and EORTC questionnaire compliance was 44/66 (67%) with no statistically significant differences between compliers (n = 44) and non-compliers (n = 22) when comparing clinicopathological parameters and survival. Univariable analyses showed that three symptoms (nausea, dry mouth, cognitive function) and two clinicopathological factors (CA 19-9 > 400 U/ml, lymph node ratio > 0.1) were significantly associated with shorter survival (p < 0.05). In multivariable analysis, cognitive function was the only independent predictor for survival: hazard ratio = 0.35 (95%CI 0.13–0.93) for high vs low cognitive function. Median survival times for patients with high and low cognitive function were 21 and 10 months, respectively (p < 0.001). Conclusion: Presurgery cognitive function is a significant independent predictor of survival in patients with resectable PDAC. Thus, presurgery patient reported outcomes may provide as strong prognostic information as clinicopathological factors. Abstract : Health-related quality of life related variables have shown to predict survival in several different types of cancers. In this prospective study, presurgery cognitive function was a significant independent predictor of survival in patients with resectable pancreatic ductal adenocarcinoma.